ANALISIS PENGARUH PENERAPAN E-PROCUREMENT TERHADAP KINERJA DAN EFISIENSI SUPPLY CHAIN MANAGEMENT Studi pada PT Petroflexx Prima Daya - , WAODE NURAFNI LILY SARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Supply Chain Management encompasses planning and management of all activities involved in the procurement and the conversion of resources as well as in the logistics management. Successful SCM in achieving its objectives nowadays cannot be separated from information technology system that creates a collaboration, coordination and integration in SCM in order to become more efficient and effective. One of the strategies undertaken by SCM in the rapidly industrial growth and competition, as well as the procurement weaknesses with the conventional systems is to implement e-procurement. The process of procurement of goods or services with e-procurement systems utilize communication and information technology facilities that used to support the general auctions electronically. It is expected that this electronic auction system would be able to answer all the current challenges occurred and be able to create the most efficient, effective and transparent ways possible of the procurement of goods or services. However, in its applications, there are some obstacles and problems in e-procurement that need to be recognized that is on the results of the implementation of e -procurement on the performance and efficiency of SCM company. The research method that used in this research is quantitative methods using a questionnaire as a means of collecting primary data. Population and sample of this research are the parties involved in the implementation of eprocurement at PT Petroflexx Prima Daya. The data obtained then were analyzed using multiple linear regression analysis to determine the impacts of the outcome variables of e-procurement implementations, either partially or simultaneously on the performance and efficiency of SCM company. The results obtained from this study, as follows: the variables that have positive and significant impacts on the performance of SCM company are centralization of management and the better data control